E-142 Mechanical thrombectomy for basilar artery acute ischemic strokes. (22nd July 2018) - Atallah, E; Hafazallah, K; Chalouhi, N; Tjoumakaris, S; Herial, N; Gooch, M; Rosenwasser, R; Zarzour, H; Jabbour, P
Abstract : Background and purpose: Neurointerventionists have been recently enthusiastic in performing endovascular mechanical thrombectomy (MT) for acute ischemic strokes of their posterior circulation(PC). Prompt repermeabilization of the PC has been linked to an increased survival rate. We aim to study the prominence, the safety and the clinical influence of PC-MT. Methods: Patient medical charts were retrospectively reviewed between 2010–2017. Data on intra-venous tissue plasminogen activator (IV-rtPA) administration, National Institute Health Stroke Scale (NIHSS; range, 0 to 42) at admission, Alberta Stroke Program Early CT Scores(ASPECTS), per-procedural complications, mortality, and clinical functional status evaluated with the modified Rankin Scale(mRS0–6) at latest follow-up, was gathered. The primary outcomes were: (1) safety of PC-MT, (2) functional independence on latest follow-up (mRS score <2), (3) functional improvement on latest follow-up defined as a de-escalation by one of the mRS score, and (4)overall mortality with delayed MT. Results: Of 234 patients, 22 (average age 60 years, 41% female) had a MT performed for their PC stroke and constituted our population. All our patients, except one, had a basilar artery stroke. One patient had a vertebral artery stroke. 2/22 (9%) patients had a history of atrial fibrillation and 4/22 (18%) received IV-rtPA. The average NIHSS at admission was 19(SD=8.2), the average DWI-ASPECTS score was 5.4, the average CT-ASPECTS score was 7.3. 2/22 (9%) patients had tandem embolus, and 3/22 (13.6%) patients had reocclusion after endovascular therapy. The average time from onset of symptoms to procedure was 12 hours (SD=8.8). 11/22 (50%) patients had a delayed MT beyond 8 hours from onset of symptoms. 10/22 (45.5%) patients performed their MT with just Second Generation Stent-Retrievers(SGSR), 2/22 (9%) patients received therapy with large-bore aspiration catheters, 10/22 (45.5%) patients received a salvage thrombus aspiration after failed first-line stent-retrievers thrombectomy. 10/22 (45.5%) patients had a first-pass successful vessel recanalization mTICI >2. The average time of revascularization was 61.6 min (SD=31.50). 20/22 (91%) had a mTICI >2 b. The average patient follow-up was 95 days (SD=105 days). The average mRS on latest follow-up was 2.2. None of our patients died at latest follow-up. 63% had a decreased mRS score reflecting an amelioration of their functional status on latest follow-up. Conclusions: We advocate for the usage of endovascular thrombectomy in patients with PC strokes. PC-MT should be performed safely beyond 8 hours from onset of symptoms. MT would reduce long-term morbi-mortality and stroke related disability in patients with PC strokes. Disclosures: E. Atallah: None. K. Hafazallah: None. N. Chalouhi: None. S. Tjoumakaris: None. N. Herial: None. M. Gooch: None. R. Rosenwasser: None. H. Zarzour: None. P. Jabbour: None.